Democratic Republic of Sao Tome and Principe : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2005)
This paper focuses on the Poverty Reduction Strategy Paper (PRSP) for the Democratic Republic of Sao Tome and Principe. The National Poverty Reduction Strategy Paper represents the result of analyses of the country's current situation as well as a set of proposals designed to rout the causes of poverty in Sao Tome and Principe in the medium to long term, based on creating the conditions that make development viable and promote the welfare of the population. This paper is prepared in response to a perception of the problems facing the country in different areas.